PENGARUH KESADARAN MEREK DAN NILAI YANG DIRASAKAN TERHADAP KEPUASAN KONSUMEN SERTA NIAT PEMBELIAN KEMBALI PRODUK PERTALITE DI KABUPATEN WAKATOBI - Laode Supardin; Alida Palilati; Sinarwaty Sinarwaty (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study was conducted with the aim to determine the effect of brand awareness and perceived value on repurchase intentions and to determine the effect of brand awareness and perceived value on consumer satisfaction and to see the mediating role of consumer satisfaction. This research was conducted in South Wangi-wangi District, Wakatobi Regency. The population of this research is all motorcycle riders who use Pertalite products in South Wangi-wangi District, Wakatobi Regency. The sample in this study was determined by 75 respondents. Data were collected using a questionnaire and processed using Partial Least Square (PLS) Version 2 M3 analysis tool.The results of this study indicate that brand awareness has a positive and significant effect on consumer satisfaction. Brand awareness has a positive and significant effect on repurchase intention. Perceived value has a positive and significant effect on consumer satisfaction. Perceived value has a positive and significant effect on repurchase intentions. Consumer satisfaction has a positive and significant effect on repurchase intentions. Consumer satisfaction mediates the effect of brand awareness on repurchase intention and its mediating nature is partial mediation. Consumer satisfaction mediates the effect of perceived value on repurchase intention and its mediating nature is partial mediation.